Effect of Weight Bearing Variations & Heel Height on Forefoot Width for Orthopaedic Imaging - Tan, Gerald; Zarugh, Adel; Toh, Eugene (Foot & ankle orthopaedics, 2022)
Category: Basic Sciences/Biologics; Midfoot/Forefoot Introduction/Purpose: The biomechanics of a foot when weight bearing change significantly due to the changes in the function through the gait cycle. Variations in heel height are known to influence load distribution in weightbearing, thus affecting change in forefoot widths. Weight bearing in radiographs are commonly used to identify these changes, which may have clinical relevance. However, there are limited studies that accurately quantify the extent of these differences in the forefoot to be analysed effectively. Hence, there is a need to investigate different weight bearing conditions and its influence on forefoot width changes required for accurate analysis of imaging. This study's aim is to evaluate the significance and degree of foot splaying with different modes of weight-bearing and heel height to achieve optimum increase in forefoot width. Methods: 32 volunteers with no clinical issues with their feet were selected for this study. Weight bearing photographs of their feet were reviewed by 2 foot and ankle surgeons (under blinded conditions) to ensure they were normal morphologically. The forefoot width is measured using sliding callipers between the medial margin of the first metatarsal head and lateral margin of the fifth metatarsal head when non weight bearing - NWB, partial weight bearing - PWB (dual leg stance) and full weight bearing - FWB (single leg stance). Single leg stance measurement is also taken at increasing heel heights of 2cm (FWB1), 4cm (FWB2) and 6cm (FWB3) using polyurethrane blocks. Each individual foot non weight-bearing width will act as its own control for the changes in the differing positions measured. Results: Statistical analysis of data demonstrated the results with the use of student t-test analysis via SPSS which showed statistically significant differences in forefoot width in both genders(p<0.05). There is an increasing trend of forefoot width as weightbearing conditions increase up to 2cm of elevated heel height. However, forefoot width decreases as heel height increases beyond 2cm in both genders. Female subjects have a higher trend of percentage of increase in mean forefoot width compared to males in all weightbearing conditions except for full weightbearing with 6cm heel height elevation. Conclusion: In conclusion, there is a linear trend of increase in forefoot width with increase from non-weightbearing up to 2cm heel height inclination. Full weightbearing with 2cm heel height inclination produces the widest foot splaying in this study. Larger future studies will need to be conducted to validate these findings.